2021
DOI: 10.26760/elkomika.v9i1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sore Throat on Changes of Vowel Sounds

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh gangguan tenggorokan terhadap perubahan karakteristik suara yang diucapkan. Karakteristik suara pada penelitian dibatasi pada aspek pitch, formant, dan pola spektrum. Spektrum suara yang

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
1
1
Order By: Relevance
“…While in this present study mean pitch F0 for vowels /e/, /i/, /o/ were found to be significant for female subjects as discussed above. On the contrary, results of present study are not in line with those reported by authors in [ 37 ] where authors reported decreases in F0 in case of male subjects due to sore throat. Reason for this may be due to increase in volume of inflamed tissues due to intracellular spaces being invaded by inflammatory exudates consisting of WBCs and fluid.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While in this present study mean pitch F0 for vowels /e/, /i/, /o/ were found to be significant for female subjects as discussed above. On the contrary, results of present study are not in line with those reported by authors in [ 37 ] where authors reported decreases in F0 in case of male subjects due to sore throat. Reason for this may be due to increase in volume of inflamed tissues due to intracellular spaces being invaded by inflammatory exudates consisting of WBCs and fluid.…”
Section: Discussioncontrasting
confidence: 99%
“…Existing study also observed that vowels /e/, /o/ and /u/ were most affected by COVID-19 infection for both genders and vowel /i/ was the least affected. This result is partly in line with findings of [ 37 ] where the authors investigated the effect of sore throat on all 5 vowels produced by male subjects and reported that vowel /a/ was most affected and vowel /i/ was the least affected vowel in the sore throat condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation